Tracking the Sugar Rush: Incorporating Continuous Glucose Monitoring Into Multisite Early Clinical Research With Type 2 Diabetes Subjects. Issue 7 (14th February 2018) - Paglialunga, Sabina; Morimoto, Bruce H.; de la Peña, Amparo; Fortier, Caroline
Abstract: Continuous glucose monitoring (CGM) systems allow patients with diabetes mellitus to closely track glucose concentrations over several days, identify trends in glucose levels, and avoid glucose excursions. This technology has not only advanced diabetes mellitus management but has increased patient safety through greater glycemic awareness. Due to these attributes, CGM is now being applied in therapeutic research as a pharmacodynamic tool to support early clinical drug development programs. However, to date only a handful of studies have utilized CGM in type 2 diabetes mellitus (T2DM) drug development. A potential barrier from fostering greater use of CGM in clinical development may be related to concerns over subject variability. Therefore, we investigated a key consideration when implementing CGM into early clinical research studies: daily variation within patients with T2DM from multiple clinical research units. From 24 patients with T2DM, we observed strong daily reproducibility (Pearson R = 0.86, P < .0001) in CGM results and found that this technique is practical for multisite studies. Altogether, with low daily variability, CGM is a powerful pharmacodynamic tool for drug efficacy and safety monitoring.